PREDIKSI INFLASI BEBERAPA KOTA DI JAWA TENGAH TAHUN 2014 MENGGUNAKAN METODE VECTOR AUTOREGRESSIVE (VAR) - Utami, Tika Nur Resa; Rusgiyono, Agus; Sugito, Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Inflation is a situation where there is an increase in the general price level. Inflation for goods and services purchased by consumers is measured by changes in the Indeks Harga Konsumen (IHK). Determination of the amount, type and quality of commodities in the package of goods and services in the IHK is based on the Survey Biaya Hidup (SBH). In Central Java, there are only four cities covered in the implementation of SBH, namely Purwokerto, Solo, Semarang, and Tegal. It was the underlying researchers took the four cities. In this case, researchers taken for the period of 2009-2013. Inflation Purwokerto, Solo, Semarang, and Tegal is a multivariate time series that show activity for a certain period. One method to analyze multivariate time series is Vector Autoregressive (VAR). VAR method is one of the multivariate time series analysis of variables that can be used to predict and assess the relationship between variables. Inflation researchers predict that by 2014 the four cities using VAR (1). Chosen VAR (1) is based on the results of some tests. VAR (1) have the optimal lag value, there is no correlation between the residual lag, and the value Root Mean Square Error (RMSE) is smaller than the other models. Keywords: Inflation, IHK, SBH, Multivariate Time Series, Forecasting, Vector Autoregressive (VAR).